POLA ASUH MAKAN IBU SERTA PREFERENSI DAN KONSUMSI SAYUR DAN BUAH ANAK USIA SEKOLAH DI BOGOR - Sophia, Annisa; Madanijah, Siti (Jurnal Gizi dan Pangan, 2014)
The aim of this study was to learn mother’s food parenting practices and school-age children’s preference and consumption of vegetables and fruits. Design of this study was a cross-sectional with purposive sampling of 108 school-age children in SDN Cibanteng 1 in rural and SDN Papandayan in urban, Bogor District. Hedonic scale and semi-quantitative food frequency questionnaire were used for measure preference and consumption of vegetables and fruits. Mothers in rural had higher score in three components of food parenting practices (mother’s role in feeding, mother’s control in child’s eating, and family eating habits) than mothers in urban. Mothers in urban had higher score in one component of food parenting practices (family eating habits of vegetables and fruits) than mothers in rural. Vegetables consumption in urban (68.5±31.6 g/day) was higher than rural (45.4±18.7 g/day). Children’s fruits consumption in urban (166.5±67.7 g/day) was higher than rural (106.9±43.0 g/day).